(untitled) (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2026)
Abstract: Digital transformation has brought significant changes across various aspects of life, including the educational system within Indonesian Islamic boarding schools (pesantren). This study aims to examine the forms of digital transformation and learning model innovations implemented by pesantren in response to the challenges of the information technology era. The research employs a library study method by reviewing various scholarly works related to the digitalization of Islamic education, curriculum development, and technology-based learning innovations. The findings reveal that digital transformation in pesantren is manifested through the utilization of online learning platforms, interactive digital media, digitalized educational administration systems, and the enhancement of digital literacy among students and educators. Emerging learning innovations include blended learning, e-learning, collaborative learning, and the integration of technology into Islamic studies. These transformations not only broaden access to learning resources but also improve the quality and effectiveness of education in adapting to contemporary developments. Nevertheless, challenges such as limited infrastructure, inadequate digital competencies, and organizational readiness remain significant concerns. Therefore, strengthening human resource capacity and ensuring sustainable policy support are essential for enabling pesantren to preserve their Islamic identity while remaining competitive in the digital age.